Hard coating film
By using a hard coat film containing an ultraviolet curing resin containing a specific weight average molecular weight sesamol type benzotriazole type ultraviolet absorber on the surface of an organic EL display, the problems of polymer degradation and durability of the light emitting element are solved, while ensuring that the color and brightness of the display are not affected.
Patent Information
- Application Number
- CN202380068230.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art is difficult to effectively suppress damage such as deterioration of polymers, fading of pigments, discoloration, etc. in organic EL displays, while improving the durability (light resistance) of the light emitting element will not adversely affect the displayed color and brightness.
UV curable resin containing sesamol-type benzotriazole-type ultraviolet absorber with a weight average molecular weight in the range of 15,000 to 35,000 was used as the material for the hard coating layer to ensure that the light transmittance of the hard coating film at 365nm, 405nm and 436nm was less than 1%, 10% and 81% respectively, respectively, and these properties were maintained after the light resistance test.
It is achieved that the durability of the light-emitting element is improved without affecting the color and brightness of the display of the organic EL display, and the display deterioration is suppressed, while the hard coat film can still maintain its original performance after the light resistance test.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a hard coating film used in an optical member, and more particularly to a hard coating film that can be used as a protective film for display device components such as organic electroluminescent (EL) display devices, liquid crystal display devices (LCD), and plasma display devices, and touch panels. Background Art
[0002] For example, the display surface of an organic electroluminescent (EL) display device, a liquid crystal display device (LCD) or the like is required to be scratch-resistant so as not to reduce visibility due to scratches during operation. Therefore, a hard coating film having a hard coating layer on a substrate film is generally used to impart scratch resistance to the display surface of the display.
[0003] In recent years, as displays have become thinner and lighter, their components have also become thinner. For example, hard coat films used in polarizing plates of displays are also required to be thinner.
[0004] In addition, for example, when the above-mentioned hard coating film is used as a protective film on the surface of an organic EL display, the hard coating film is required to meet several requirements, such as not causing adverse effects on the color and brightness displayed by the organic EL display, being able to improve the durability (light resistance) of the light-emitting element of the organic EL display, and being able to inhibit display degradation of the organic EL display.
[0005] As a prior art, for example, Patent Document 1 discloses a film-forming composition containing a triazine ring-containing polymer capable of forming a thin film having a high refractive index and excellent light resistance. Also, for example, Patent Document 2 discloses a film-forming composition containing a triazine ring-containing hyperbranched polymer capable of forming a film having high transparency and high light resistance and having a thickness of 1000 nm or more.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2017 / 110810
[0009] Patent Document 2: International Publication No. 2013 / 094664 Summary of the invention
[0010] Problems to be solved by the invention
[0011] In order to suppress the degradation of some polymers used in organic EL displays, the fading of pigments, discoloration and other damages, it is required to fully reduce the transmittance under the wavelength represented by 365nm and 405nm. In addition, in order to improve the durability (light resistance) of the light-emitting element of the organic EL display in recent years, it is required to fully reduce the transmittance of 405nm for example in order to protect the light-emitting element. However, the transmittance of the film obtained by the film-forming composition disclosed in the above-mentioned patent documents 1 and 2, for example, under 365nm and 405nm is very high, which cannot solve the problem of suppressing the degradation of some polymers used in the above-mentioned organic EL display, the fading of pigments, discoloration and other damages, and improving the durability (light resistance) of the light-emitting element of the organic EL display.
[0012] In addition, in addition to the above-mentioned patent documents 1 and 2, various hard coating films of the prior art are also known, but it is difficult to obtain a hard coating film that can simultaneously meet the requirements of not causing adverse effects on the color and brightness of the display of the above-mentioned organic EL display, being able to improve the durability (light resistance) of the light-emitting element of the organic EL display, and being able to inhibit the display degradation of the organic EL display.
[0013] Therefore, the objects of the present invention are, first, to provide a hard coating film which, when used as a protective film on the surface of an organic EL display, will not adversely affect the color and brightness of the display of the organic EL display, and can improve the durability (light resistance) of the light-emitting element of the organic EL display and can inhibit the display degradation of the organic EL display; second, to provide a hard coating film which can maintain the above-mentioned properties even after the hard coating film is subjected to a light resistance test; and third, to provide a hard coating film which can be thinned.
[0014] Means for solving problems
[0015] The present inventors have conducted intensive studies to solve the above problems, and as a result, have found that the above problems can be solved by the invention having the following configuration.
[0016] That is, the present invention has the following configurations.
[0017] (First Invention)
[0018] A hard coating film, characterized in that a hard coating layer is laminated on at least one surface of a transparent substrate, the hard coating layer comprises an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000, the transmittance of the hard coating film at a wavelength of 365 nm is less than 1%, the transmittance at a wavelength of 405 nm is less than 10%, and the transmittance at a wavelength of 436 nm is 81% or more.
[0019] (Second Invention)
[0020] The hard coating film as described in the first invention is characterized in that, after the hard coating film is subjected to an accelerated light resistance test according to JIS-K-5600-7-7 for 100 hours, the transmittance at a wavelength of 365 nm is less than 1%, the transmittance at a wavelength of 405 nm is less than 10%, and the transmittance at a wavelength of 436 nm is greater than 81%.
[0021] (Third Invention)
[0022] The hard coating film according to the first or second invention is characterized in that the thickness of the hard coating layer is greater than 2.0 μm and less than 6.0 μm.
[0023] (Fourth Invention)
[0024] The hard coating film according to any one of the first to third inventions is characterized in that the amount of the sesamol-type benzotriazole ultraviolet absorber blended is 20 to 60 parts by mass based on 100 parts by mass of the ultraviolet curable resin of the hard coating layer.
[0025] (Fifth Invention)
[0026] The hard coating film according to any one of the first to fourth inventions is characterized in that the transparent substrate is a triacetyl cellulose film, a polyethylene terephthalate film or a cycloolefin polymer film.
[0027] (Sixth Invention)
[0028] The hard coat film according to the first or second invention is characterized in that an easy-adhesion layer is provided between the transparent substrate and the hard coat layer.
[0029] Effects of the Invention
[0030] According to the present invention, a hard coating film can be provided which, when used as a protective film on the surface of an organic EL display, does not adversely affect the color and brightness of the display of the organic EL display, and can improve the durability (light resistance) of the light-emitting element of the organic EL display and can inhibit display degradation of the organic EL display.
[0031] Furthermore, according to the present invention, it is possible to provide a hard coating film which can maintain the above-mentioned performance even after the hard coating film is subjected to a light resistance test.
[0032] Furthermore, according to the present invention, a hard coating film that can be reduced in thickness can be provided. DETAILED DESCRIPTION
[0033] Hereinafter, the mode for carrying out the present invention will be described in detail, but the present invention is not limited to the following embodiment.
[0034] In addition, in this specification, unless otherwise specified, "○○ to △△" means "not less than ○○ and not more than △△".
[0035] As described in the first invention, the hard coating film of the present invention is characterized in that the hard coating film has a hard coating layer laminated on at least one surface of a transparent substrate, the hard coating layer comprises an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000, the transmittance of the hard coating film at a wavelength of 365 nm is less than 1%, the transmittance at a wavelength of 405 nm is less than 10%, and the transmittance at a wavelength of 436 nm is 81% or more.
[0036] Hereinafter, the structure of the hard coating film of the present invention will be described in detail.
[0037] [Transparent substrate]
[0038] First, the transparent substrate of the hard coat film will be described.
[0039] As the substrate to be coated with the hard coating film of the present invention, a transparent film substrate is generally used.
[0040] The transparent film substrate used in the present invention is not particularly limited as long as it has transparency, and examples thereof include resin films comprising acrylic resins, triacetyl cellulose, polyethylene terephthalate, cycloolefin polymers, polycarbonate, polyethylene naphthalate, polyethylene, polypropylene terephthalate, polypropylene, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polymethyl methacrylate, polystyrene glycidyl methacrylate, aromatic polyimide, alicyclic polyimide, polyamide-imide, and mixtures thereof.
[0041] Here, the term "transparency" means that the total light transmittance measured in accordance with JIS-K7136 is 80% or more.
[0042] In the present invention, from the viewpoint of transparency, optical properties and versatility of the optical film for display, among these film substrates, triacetyl cellulose film, polyethylene terephthalate film, cycloolefin polymer film and the like are particularly preferred.
[0043] In the present invention, the thickness of the transparent substrate is appropriately selected according to the application, and is preferably 50 μm or less, particularly preferably 30 μm or less, from the viewpoint of thin-filming requirements of the hard coating film accompanying the thin-filming and lightweight display. On the other hand, from the viewpoint of mechanical strength, handling properties, etc., it is preferably 10 μm or more.
[0044] [Hard coating]
[0045] Next, the hard coating layer of the hard coating film will be described.
[0046] In the present invention, the hard coat layer contains at least an ultraviolet curable resin and a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000.
[0047] In the present invention, as the resin contained in the above-mentioned hard coating layer, it is preferred to use an ultraviolet curing resin, especially from the perspective of imparting surface hardness (pencil hardness, scratch resistance) to the hard coating layer and being able to adjust the degree of crosslinking by the amount of ultraviolet light exposure and the surface hardness of the hard coating layer.
[0048] The ultraviolet curable resin used in the present invention is not particularly limited as long as it is a transparent resin cured by irradiating ultraviolet rays (UV). In order to achieve the hardness of the coating film and the hard coating layer forms a three-dimensional cross-linked structure, it is preferably contained in a multifunctional acrylate that can be cured by UV and has more than 3 (meth) acryloyloxy groups in one molecule. As a specific example of a multifunctional acrylate that can be cured by UV and has more than 3 (meth) acryloyloxy groups in the molecule, it can be listed as: trimethylolpropane tri(meth) acrylate, pentaerythritol tri(meth) acrylate, pentaerythritol tetra(meth) acrylate, dipentaerythritol tri(meth) acrylate, dipentaerythritol tetra(meth) acrylate, dipentaerythritol penta(meth) acrylate, dipentaerythritol hexa(meth) acrylate, trimethylolpropane ethoxy triacrylate, glycerol propoxy triacrylate, ditrimethylolpropane tetraacrylate, etc. It should be noted that the multifunctional acrylate can be used not only alone, but also in combination of two or more.
[0049] In addition, the ultraviolet curable resin used in the above-mentioned hard coat preferably uses a monomer or oligomer or polymer with a weight average molecular weight in the range of 500 to 3600, more preferably a weight average molecular weight in the range of 500 to 3000, and further preferably a weight average molecular weight of 500 to 2400. When the weight average molecular weight is less than 500, the curing shrinkage during curing by UV irradiation is large, the phenomenon of warping (curling) of the hard coat film toward the hard coat surface side becomes larger, and the subsequent processing steps produce undesirable conditions and poor processing adaptability. In addition, when the weight average molecular weight is greater than 3600, the softness of the hard coat is improved, but the hardness is insufficient, so it is not suitable.
[0050] In addition, the weight average molecular weight in the present invention is an average molecular weight obtained by standard polystyrene conversion analyzed by gel permeation chromatography (GPC).
[0051] In addition, when the weight average molecular weight of the ultraviolet curable resin used in the hard coat layer is less than 1500, the number of functional groups in one molecule is preferably 3 or more and less than 10. In addition, when the weight average molecular weight of the ultraviolet curable resin is more than 1500, the number of functional groups in one molecule is preferably 3 or more and less than 20. If it is within the above range, curling can be suppressed and appropriate processing adaptability can be maintained.
[0052] In addition, as the resin contained in the above-mentioned hard coating layer, on the basis of including the above-mentioned ultraviolet curing resin, it is also possible to mix|blend with thermoplastic resins such as polyethylene, polypropylene, polystyrene, polycarbonate, polyester, acrylic, styrene-acrylic, cellulose, etc.; phenolic resin, urea resin, unsaturated polyester, epoxy resin, silicone resin, etc. thermosetting resin within the range which does not impair the hardness and abrasion resistance of the hard coating layer.
[0053] In the present invention, the hard coat layer contains the ultraviolet curable resin and further contains a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000 (hereinafter sometimes referred to as "ultraviolet absorber of the present invention" in this specification).
[0054] The ultraviolet absorber of the present invention is formed by reacting and polymerizing a sesamol-type benzotriazole monomer with, for example, an acrylate resin component.
[0055] Here, the sesamol-type benzotriazole monomer refers to, for example, a substance represented by the following general formula (I), and is a derivative derived from a compound in which sesamol is bonded to the nitrogen atom at the 2-position of the benzotriazole ring.
[0056]
[0057] In the above formula, R1 represents a hydrogen atom or a methyl group. In addition, R2 represents a linear or branched alkylene group having 1 to 6 carbon atoms or a linear or branched oxyalkylene group having 1 to 6 carbon atoms.
[0058] Specific examples of the sesamol-type benzotriazole monomer represented by the general formula (I) include 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]ethyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]ethyl acrylate, 3-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl methacrylate, 3-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl methacrylate, 4-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl methacrylate, 4-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl acrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yloxy]ethyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yloxy]ethyl acrylate, 2-[3- {2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl methacrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl acrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]butyl methacrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]butyl Acrylates, 2-(methacryloyloxy)ethyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 2-(acryloyloxy)ethyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 4-(methacryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 4-(acryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, and the like.
[0059] The ultraviolet absorber of the present invention can be obtained by polymerizing the above-mentioned sesamol-type benzotriazole monomer with other monomer components (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate and other acrylic resin components). The polymerization method can be a conventionally known solution polymerization method, emulsion polymerization method, suspension polymerization method, bulk polymerization method, etc.
[0060] In the present invention, it is important to use a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000.
[0061] In contrast, when a sesamol-type benzotriazole ultraviolet light absorber having a weight average molecular weight of less than 15,000 is used, as shown in the comparative example described later, the transmittance at 405 nm cannot be sufficiently reduced, so there is a problem of display degradation of the organic EL display. In addition, when a sesamol-type benzotriazole ultraviolet light absorber having a weight average molecular weight of greater than 35,000 is used, its performance cannot be maintained after a light resistance test at a wavelength of 405 nm, there is a problem of display degradation of the organic EL display and a problem of not being able to achieve improvement in the durability (light resistance) of the light-emitting element.
[0062] The weight average molecular weight of the sesamol-type benzotriazole ultraviolet absorber is an average molecular weight calculated in terms of standard polystyrene analyzed by gel permeation chromatography (GPC).
[0063] The ultraviolet absorber of the present invention may be used alone or in combination of two or more.
[0064] Furthermore, for example, other benzotriazole-based ultraviolet absorbers, hydroxyphenyltriazine-based ultraviolet absorbers, etc. may be used in combination within a range not impairing the effects of the present invention.
[0065] The hard coat film of the present invention can satisfy the range of the present invention in terms of spectral characteristics (light transmittance at wavelengths of 365 nm, 405 nm, and 436 nm) by containing the ultraviolet absorber of the present invention in the hard coat layer.
[0066] As described later, in the present invention, the thickness of the hard coat layer containing the ultraviolet absorber of the present invention is preferably greater than 2.0 μm and less than 6.0 μm, and is particularly preferably in the range of 3.0 μm to 5.0 μm. When the thickness of the hard coat layer is greater than 2.0 μm and less than 6.0 μm, the amount of the ultraviolet absorber of the present invention is preferably in the range of 20 to 60 parts by mass relative to 100 parts by mass of the ultraviolet curable resin of the hard coat layer. When the amount of the ultraviolet absorber of the present invention is less than 20 parts by mass, the spectral characteristics of the present invention cannot be fully satisfied within the range of the thickness of the hard coat layer of the present invention being greater than 2.0 μm and less than 6.0 μm. On the other hand, when the amount of the ultraviolet absorber of the present invention is greater than 60 parts by mass, the ratio of the ultraviolet curable resin in the hard coat layer is reduced, so there is a situation where the adhesion of the hard coat layer to the film substrate is reduced or the hardness of the hard coat layer is reduced, so it is not suitable.
[0067] When the thickness of the hard coat layer is set to be in the range of 3.0 μm to 5.0 μm, the blending amount of the ultraviolet absorber of the present invention is preferably in the range of 30 to 50 parts by mass based on 100 parts by mass of the ultraviolet curable resin of the hard coat layer.
[0068] In addition, inorganic oxide particles can also be contained in the hard coat layer to further improve the surface hardness (scratch resistance). In this case, the average particle size of the inorganic oxide particles is preferably in the range of 5nm to 50nm, and more preferably in the range of 10nm to 40nm. When the average particle size is less than 5nm, it is difficult to obtain sufficient surface hardness. On the other hand, when the average particle size is greater than 50nm, the gloss and transparency of the hard coat layer are easily reduced, and the flexibility may also be reduced.
[0069] In the present invention, examples of the inorganic oxide fine particles include alumina, silica, etc. Among these, alumina containing aluminum as a main component is particularly preferred because it has high hardness and can achieve the effect with a smaller addition amount than silica.
[0070] In the present invention, the content of the inorganic oxide particles is preferably 0.1 to 10.0 parts by mass relative to 100 parts by mass of the ultraviolet curable resin of the hard coat layer. When the content of the inorganic oxide particles is less than 0.1 parts by mass, it is difficult to obtain an effect of improving the surface hardness (scratch resistance). On the other hand, when the content of the inorganic oxide particles is greater than 10.0 parts by mass, the haze increases, so it is not preferred.
[0071] The hard coating paint used to form the hard coating layer may contain a photopolymerization initiator. As such a photopolymerization initiator, commercially available acetophenones such as IRGACURE 651 and IRGACURE 184 (both trade names: manufactured by BASF) and benzophenones such as IRGACURE 500 (trade name: manufactured by BASF) can be used.
[0072] For the purpose of improving coating properties, a leveling agent can be used in the above-mentioned hard coating layer, and known leveling agents such as fluorine, acrylic, siloxane, and their adducts or mixtures can be used. For the amount of mixing, it can be mixed in the range of 0.03 to 3.0 parts by mass relative to 100 parts by mass of the solid content of the resin of the hard coating layer. In addition, in touch panel applications, in the case of using an optically transparent adhesive OCR for the purpose of bonding with the protective glass (CG) of the touch panel terminal, a transparent conductive component (TSP), a liquid crystal module (LCM), etc., it is preferred to use an acrylic leveling agent with a high surface free energy (about 30 mN / m or more) and a fluorine leveling agent.
[0073] As other additives added to the hard coat layer, defoaming agents, surface tension adjusters, antifouling agents, antioxidants, antistatic agents, light stabilizers, etc. may be blended as needed within a range not impairing the effects of the present invention.
[0074] The hard coating layer is formed by applying a hard coating coating on the transparent substrate, drying it, and then curing it by UV irradiation. The hard coating coating is obtained by dissolving and dispersing the ultraviolet curable resin and the ultraviolet absorber, photopolymerization initiator, other additives, etc. of the present invention in a suitable solvent. The solvent can be appropriately selected according to the solubility of the above-mentioned resin to be matched, and can be a solvent that can at least uniformly dissolve or disperse the solid components (resin, ultraviolet absorber, pigment, photopolymerization initiator, other additives, etc.). As such a solvent, aromatic solvents such as toluene, xylene, and n-heptane; aliphatic solvents such as cyclohexane, methylcyclohexane, and ethylcyclohexane; ester solvents such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, and methyl lactate; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; alcohol solvents such as methanol, ethanol, isopropanol, and n-propanol, etc., and other known organic solvents can be used alone or in appropriate combinations.
[0075] There is no particular restriction on the coating method of the hard coating coating for forming the above-mentioned hard coating layer. It can be coated by known coating methods such as gravure coating, micro gravure coating, injection doctor bar coating, slide die coating, slit die coating, screen printing, spray coating, etc., and then usually dried at a temperature of about 50°C to about 120°C.
[0076] The amount of ultraviolet (UV) irradiation after the hard coat layer is formed may be an amount required for the hard coat layer to have sufficient hardness, and may be appropriately set according to the type of ultraviolet curable resin and the like.
[0077] In the present invention, the thickness of the hard coat layer (coating film thickness) is, for example, preferably greater than 2.0 μm and less than 6.0 μm, and more preferably in the range of 3.0 μm to 5.0 μm.
[0078] When the thickness of the hard coating layer is less than 2.0 μm, the required hardness (e.g., scratch resistance) is reduced, so it is not preferred. In addition, when the thickness of the hard coating layer is 6.0 μm or more, strong curling is likely to occur, and the operability in the manufacturing process is reduced, so it is not preferred from the perspective of thin film hard coating.
[0079] It should be noted that the hard coat film of the present invention is formed by laminating the above-mentioned hard coat layer on at least one side of a transparent substrate. However, when a cycloolefin polymer film is used as the transparent substrate, in order to improve the adhesion of the hard coat layer, it is also preferred to provide an easy-adhesion layer between the transparent substrate and the hard coat layer.
[0080] As the resin used in the above-mentioned easy-adhesion layer, any resin that forms a coating can be used without particular limitation. For example, from the viewpoint of adhesion to the above-mentioned transparent substrate film (cycloolefin film), polyolefin resins, styrene acrylic resins, acrylic resins such as methyl methacrylate resins, epoxy resins, isocyanate resins, cellulose resins, or a mixture of two or more of these resins can be preferably used.
[0081] The coating thickness of the easy-adhesion layer is not particularly limited, but is preferably in the range of 0.1 μm to 5.0 μm so as not to adversely affect the adhesion between the substrate film and the hard coat layer or the pencil hardness of the hard coat layer.
[0082] As described above, the hard coating film of the present invention is formed by laminating a hard coating layer on at least one surface of a transparent substrate, the hard coating layer comprising an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000.
[0083] Furthermore, the hard coating film of the present invention is characterized by satisfying the following spectral characteristics.
[0084] That is, the hard coating film of the present invention is characterized in that the light transmittance at a wavelength of 365 nm is less than 1%, the light transmittance at a wavelength of 405 nm is less than 10%, and the light transmittance at a wavelength of 436 nm is 81% or more.
[0085] It should be noted that a specific method for measuring the light transmittance at each of the above wavelengths will be described in the examples described later.
[0086] The hard coating film of the present invention is provided with a hard coating layer comprising an ultraviolet curable resin containing the ultraviolet absorber of the present invention, and the above-mentioned spectral characteristics (light transmittance at each wavelength of 365nm, 405nm and 436nm) meet the scope of the present invention, and can suppress the light transmittance at wavelengths represented by 365nm and 405nm, which will cause damage such as deterioration of some polymers used in organic EL displays, fading and discoloration of pigments, to less than 10%, and can suppress the deterioration of some polymers, fading and discoloration of pigments, etc. In addition, for the purpose of improving the durability (light resistance) of the light-emitting element of the organic EL display in recent years, it is required to sufficiently reduce the light transmittance at 405nm in order to protect the light-emitting element, and the hard coating film of the present invention can suppress the light transmittance at a wavelength of 405nm to less than 10%, and can improve the durability (light resistance) of the light-emitting element of the organic EL display in recent years. Moreover, in order to ensure the display brightness of the organic EL display, it is required to make the transmittance at a wavelength of 436nm in the visible light region as large as possible. The hard coating film of the present invention can obtain a transmittance of more than 81% at a wavelength of 436nm in the visible light region, and will not cause adverse effects on the display brightness of the organic EL display.
[0087] The hard coating film of the present invention is also characterized in that after the hard coating film is subjected to an accelerated light resistance test according to JIS-K-5600-7-7 for 100 hours, the light transmittance at a wavelength of 365 nm is less than 1%, the light transmittance at a wavelength of 405 nm is less than 10%, and the light transmittance at a wavelength of 436 nm is 81% or more.
[0088] In addition, the above-mentioned light resistance test will be described in more detail in the description of the examples to be described later.
[0089] For the transmittance of each wavelength mentioned above, from the purpose, it is necessary to maintain its performance after the light resistance test at wavelengths of 365nm and 405nm, which cause damage such as degradation of some polymers, fading and discoloration of pigments, and at a wavelength of 405nm, which helps to protect the light-emitting elements of organic EL displays in recent years. The hard coating film of the present invention is provided with a hard coating layer comprising an ultraviolet curable resin containing the ultraviolet absorber of the present invention, which can suppress the increase of the transmittance at wavelengths of 365nm and 405nm after the light resistance test, and can suppress the display degradation of the organic EL display. It should be noted that for the wavelength of 436nm in the visible light region, the hard coating film of the present invention can also suppress the increase of the transmittance after the light resistance test, and can maintain the display brightness of the organic EL display.
[0090] As described in detail above, according to the present invention, when used as a protective film on the surface of an organic EL display, a hard coating film can be obtained that does not adversely affect the color and brightness of the display of the organic EL display, and can improve the durability (light resistance) of the light-emitting element of the organic EL display and can inhibit the display degradation of the organic EL display. In addition, according to the present invention, a hard coating film that can maintain the above-mentioned performance even after the hard coating film is subjected to a light resistance test can be obtained. In addition, according to the present invention, a hard coating film that can be thinned can be obtained.
[0091] Example
[0092] Next, the embodiments of the present invention will be described in more detail with reference to examples. However, the present invention is not limited to the following examples.
[0093] In addition, in the following description, unless otherwise stated, "part" means a mass part, and unless otherwise stated, "%" means mass %.
[0094] (Example 1)
[0095] [Preparation of coating liquid for forming hard coat layer]
[0096] 94 parts of an acrylate ultraviolet curing resin coating (HFC-UVA-13 (trade name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of the sesamol-type benzotriazole ultraviolet absorber; 22,000) containing the sesamol-type benzotriazole ultraviolet absorber of the present invention is used as a main agent, and 5 parts of Irgacure 184 (photopolymerization initiator, manufactured by BASF) and 1 part of a surface modifier (Ftergent 681; manufactured by Neos Co., Ltd.) are added, and diluted with toluene / propylene glycol monomethyl ether acetate = 15 / 85 (parts by weight) to prepare a coating liquid for forming a hard coat layer (hereinafter also referred to as "hard coat layer coating") having a final solid content concentration of 30%.
[0097] [Production of hard coating]
[0098] The hard coating material was applied to one side of a triacetyl cellulose film TJ25UL (manufactured by Fujifilm Corporation) having a thickness of 25 μm using a bar coater, and hot air dried for 1 minute in a drying oven at 80° C., thereby forming a coating layer having a thickness of 3.0 μm. A UV irradiation device was set at a height of 60 mm from the coating surface, and the UV irradiation amount was 100 mJ / cm 2 The hard coating film of Example 1 was prepared by curing the hard coating film by ultraviolet irradiation.
[0099] (Example 2)
[0100] A hard coating layer was prepared in the same manner as in Example 1, except that an acrylate UV-curable resin coating (HFC-UVA-13 (trade name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of the sesamol-benzotriazole UV absorber; 27,000) containing the sesamol-benzotriazole UV absorber of the present invention was used as the acrylate UV-curable resin coating. The hard coating layer was then used to prepare a hard coating film of Example 2 in the same manner as in Example 1.
[0101] (Example 3)
[0102] A hard coating layer was prepared in the same manner as in Example 1, except that an acrylate UV-curable resin coating (HFC-UVA-13 (trade name); manufactured by Harima Chemicals, Ltd.; weight average molecular weight of the sesamol-benzotriazole UV absorber; 35,000) containing the sesamol-benzotriazole UV absorber of the present invention was used as the acrylate UV-curable resin coating. The hard coating layer was then used to prepare a hard coating film of Example 3 in the same manner as in Example 1.
[0103] (Example 4)
[0104] A hard coating layer was prepared in the same manner as in Example 1, except that an acrylate UV-curable resin coating (HFC-UVA-13 (trade name); manufactured by Harima Chemicals, Ltd.; weight average molecular weight of the sesamol-benzotriazole UV absorber; 15,000) containing the sesamol-benzotriazole UV absorber of the present invention was used as the acrylate UV-curable resin coating. The hard coating layer was then used to prepare a hard coating film of Example 4 in the same manner as in Example 1.
[0105] (Example 5)
[0106] A hard coat film of Example 5 was produced in the same manner as in Example 1, using the hard coat paint of Example 1, except that the substrate was changed to A4360 (manufactured by Toyobo Co., Ltd.) having a thickness of 50 μm as a polyethylene terephthalate film.
[0107] (Example 6)
[0108] A hard coat film of Example 6 was prepared by using the hard coat paint of Example 1 in the same manner as in Example 1 except that the substrate was changed to ZEONOR Film ZF12 (manufactured by ZEONOR Co., Ltd.) having a thickness of 13 μm as a cycloolefin polymer film.
[0109] (Example 7)
[0110] A hard coat film of Example 7 was prepared by using the hard coat paint of Example 1 in the same manner as in Example 1 except that the substrate was changed to ZEONOR Film ZD12 (manufactured by ZEONOR Co., Ltd.) having a thickness of 22 μm as a cycloolefin polymer film.
[0111] (Example 8)
[0112] A hard coat film of Example 8 was prepared by using the hard coat paint of Example 1 in the same manner as in Example 1 except that the substrate was changed to ZEONOR Film ZD12 (manufactured by ZEONOR Co., Ltd.) having a thickness of 26 μm as a cycloolefin polymer film.
[0113] (Example 9)
[0114] A hard coating film of Example 9 was produced in the same manner as in Example 8 except that the coating film thickness of the coating layer of Example 8 was changed to 5.0 μm.
[0115] (Comparative Example 1)
[0116] [Preparation of coating material for hard coat]
[0117] 94 parts of an acrylate UV-curable resin coating containing a sesamol-type benzotriazole UV absorber (HFC-UVA-13 (trade name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of the sesamol-type benzotriazole UV absorber; 13,000) was used as the main agent, and 5 parts of Irgacure 184 (photopolymerization initiator, manufactured by BASF) and 1 part of a surface modifier (Ftergent 681; manufactured by Neos Co., Ltd.) were added, and diluted with toluene / propylene glycol monomethyl ether acetate = 15 / 85 (parts by weight) to prepare a hard coating coating with a final solid content concentration of 30%.
[0118] [Production of hard coating]
[0119] A hard coating film of Comparative Example 1 was produced in the same manner as in Example 1 except that the hard coating paint having the above composition was used.
[0120] (Comparative Example 2)
[0121] A hard coating film of Comparative Example 2 was produced in the same manner as in Comparative Example 1 except that the coating film thickness of the coating layer of Comparative Example 1 was changed to 5.0 μm.
[0122] (Comparative Example 3)
[0123] A hard coating layer was prepared in the same manner as in Comparative Example 1, except that an acrylate UV-curable resin coating containing a sesamol-type benzotriazole UV absorber (HFC-UVA-13 (trade name); manufactured by Harima Chemicals Co., Ltd.; weight average molecular weight of the sesamol-type benzotriazole UV absorber; 37,000) was used as the acrylate UV-curable resin coating. The hard coating layer was then used to prepare a hard coating film of Comparative Example 3 in the same manner as in Comparative Example 1.
[0124] (Comparative Example 4)
[0125] A hard coating film of Comparative Example 4 was produced in the same manner as in Comparative Example 3 except that the coating film thickness of the coating layer of Comparative Example 3 was changed to 5.0 μm.
[0126] (Comparative Example 5)
[0127] [Preparation of coating material for hard coat]
[0128] 84 parts of an acrylate UV-curable resin (NK Ester A-9550 (trade name); manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) were used as the main agent, and 10 parts of a benzotriazole UV absorber (Adecastab LA-36 (trade name); manufactured by ADEKA Corporation), 5 parts of Irgacure 184 (photopolymerization initiator, manufactured by BASF), and 1 part of a surface modifier (Ftergent 681; manufactured by Neos Corporation) were added, and diluted with toluene / propylene glycol monomethyl ether acetate = 15 / 85 (parts by weight) to prepare a hard coating material with a final solid content concentration of 30%.
[0129] [Production of hard coating]
[0130] A hard coating film of Comparative Example 5 was produced in the same manner as in Example 1 except that the hard coating paint having the above composition was used.
[0131] (Comparative Example 6)
[0132] [Preparation of coating material for hard coat]
[0133] 90 parts of an acrylate ultraviolet curable resin (NK Ester A-9550 (trade name); manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) was used as the main agent, and 4 parts of anthocyanin (NK-9994 (trade name); manufactured by Hayashibara Co., Ltd.), 5 parts of Irgacure 184 (photopolymerization initiator, manufactured by BASF), and 1 part of a surface modifier (Ftergent 681; manufactured by Neos Co., Ltd.) were added, and diluted with toluene / propylene glycol monomethyl ether acetate = 15 / 85 (parts by weight) to prepare a hard coating material with a final solid content concentration of 30%.
[0134] [Production of hard coating]
[0135] A hard coating film of Comparative Example 6 was produced in the same manner as in Example 1 except that the hard coating paint having the above composition was used.
[0136] <Evaluation>
[0137] The hard coating films of Examples and Comparative Examples prepared as described above were evaluated according to the following items. Table 1 shows the results in summary.
[0138] <Thickness of coating film>
[0139] The thickness of the coating film of the hard coat layer (HC layer) was measured using Thin-Film Analyzer F20 (trade name) (manufactured by FILMETRICS).
[0140] <Light transmittance at each wavelength>
[0141] The light transmittance of the hard coating film at each wavelength (365 nm, 405 nm, 436 nm) was measured using a spectrophotometer U-3310 manufactured by Hitachi High-Technologies Corporation. The measurement was performed under the conditions of a wavelength range of 250 nm to 800 nm and a scanning rate of 600 nm / min.
[0142] <Light resistance test>
[0143] Each hard coating film produced in Examples and Comparative Examples was subjected to an accelerated light resistance test using a Xenon Weather Ometer (performed under the following conditions in accordance with JIS-K-5600-7-7).
[0144] Light source: Xenon arc
[0145] Temperature: 63℃
[0146] Relative humidity: 50%
[0147] Irradiance: 50W / m 2
[0148] Radiation time: 100 hours
[0149] Rainfall period and time: Not set
[0150] In addition, the light transmittance of the hard coating film at each wavelength after the light resistance test was measured in the same manner as above.
[0151]
[0152] As can be seen from the results of Table 1 above, the hard coating film of the embodiment of the present invention can suppress the transmittance at wavelengths represented by 365nm and 405nm, which cause damages such as degradation of some polymers used in organic EL displays, fading and discoloration of pigments, to less than 10%, by providing a hard coating layer containing an ultraviolet curable resin containing an ultraviolet absorber of the present invention, and the above spectral characteristics (transmittance at each wavelength of 365nm, 405nm and 436nm) meet the scope of the present invention, and can suppress the degradation of some polymers, fading and discoloration of pigments, etc. In addition, in order to improve the durability (light resistance) of the light-emitting element of the organic EL display in recent years, it is required to sufficiently reduce the transmittance at 405nm in order to protect the light-emitting element, and the hard coating film of the embodiment of the present invention can suppress the transmittance at a wavelength of 405nm to less than 10%, and can improve the durability (light resistance) of the light-emitting element of the organic EL display in recent years. Moreover, for the wavelength of 436nm in the visible light region, in order to ensure the display brightness of the organic EL display, the transmittance of the wavelength of 436nm in the visible light region is required to be as large as possible. The hard coating film of the embodiment of the present invention can obtain a transmittance of more than 81% at a wavelength of 436nm in the visible light region, and will not cause adverse effects on the display brightness of the organic EL display.
[0153] In addition, for the transmittance of each wavelength mentioned above, from the purpose, it is necessary to maintain its performance after the light resistance test at wavelengths of 365nm and 405nm, which cause damage such as degradation of some polymers, fading and discoloration of pigments, and at a wavelength of 405nm, which helps protect the light-emitting elements of organic EL displays in recent years. The hard coating film of the embodiment of the present invention can suppress the increase of the transmittance at wavelengths of 365nm and 405nm after the light resistance test by providing a hard coating layer containing an ultraviolet curable resin containing the sesamol-type benzotriazole ultraviolet absorber of the present invention, and can suppress the display degradation of the organic EL display. It should be noted that for the wavelength of 436nm in the visible light region, the hard coating film of the embodiment of the present invention can also suppress the increase of the transmittance after the light resistance test and can maintain the display brightness of the organic EL display.
[0154] In contrast, in the hard coating film of Comparative Example 1 provided with a hard coating layer of an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight of less than 15,000, the transmittance at 405 nm cannot be sufficiently reduced, so there is a problem of display degradation of the organic EL display. In addition, in the hard coating film of Comparative Example 2, although the transmittance at 405 nm can be reduced by adjusting the film thickness (thickening) of the hard coating layer of Comparative Example 1, its performance cannot be maintained after the light resistance test at a wavelength of 405 nm, and there is a problem of display degradation of the organic EL display and a problem of not being able to achieve the durability (light resistance) of the light-emitting element. It should be noted that a method of further thickening the film thickness of the hard coating layer (for example, more than 6.0 μm) and maintaining its performance after the light resistance test at a wavelength of 405 nm can be considered, but the thickening of the hard coating layer is contrary to the technical trend of curling of the hard coating layer, cracking of the hard coating layer, and thin filmization of the hard coating layer, and is therefore not preferred.
[0155] In addition, in the hard coating film of Comparative Example 3 provided with a hard coating layer comprising an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight greater than 35,000, the performance cannot be maintained even after the light resistance test at a wavelength of 405 nm, and there is a problem of display degradation of the organic EL display and a problem of not being able to improve the durability (light resistance) of the light-emitting element. In addition, in the hard coating film of Comparative Example 4, although the performance can be maintained even after the light resistance test at a wavelength of 405 nm by adjusting the film thickness (thickening) of the hard coating layer of Comparative Example 3, the performance cannot be maintained after the light resistance test at a wavelength of 436 nm, and there is a problem of not being able to fully ensure the display brightness of the organic EL display. It should be noted that a method of further increasing the film thickness of the hard coat layer (for example, 6.0 μm or more) and maintaining its performance even after a light resistance test at a wavelength of 436 nm can be considered, but thickening the hard coat layer is contrary to the technical trend of curling of the hard coat layer, cracking of the hard coat layer, and thinning of the hard coat layer, and is therefore not preferred.
[0156] In addition, in the hard coating film of Comparative Example 5 using an ultraviolet absorber other than the ultraviolet absorber of the present invention, the transmittance at a wavelength of 405 nm cannot be sufficiently reduced, so there is a problem that the protection of the organic EL display cannot be achieved. In addition, in the hard coating film of Comparative Example 6 not using the ultraviolet absorber of the present invention, although there is no problem with the initial transmittance at each wavelength, the change in the transmittance at each wavelength after the light resistance test is extremely large, and there is a problem that the durability (light resistance) of the light emitting element of the organic EL display cannot be improved.
Claims
1. A hard coating film, characterized in that: The hard coating film has a hard coating layer stacked on at least one side of a transparent substrate, the hard coating layer comprising an ultraviolet curable resin containing a sesamol-type benzotriazole ultraviolet absorber having a weight average molecular weight in the range of 15,000 to 35,000, the transmittance of the hard coating film at a wavelength of 365 nm is less than 1%, the transmittance at a wavelength of 405 nm is less than 10%, and the transmittance at a wavelength of 436 nm is greater than 81%.
2. The hard coating film according to claim 1, wherein After the hard coating film is subjected to an accelerated light resistance test according to JIS-K-5600-7-7 for 100 hours, the transmittance at a wavelength of 365 nm is less than 1%, the transmittance at a wavelength of 405 nm is less than 10%, and the transmittance at a wavelength of 436 nm is 81% or more.
3. The hard coating film according to claim 1 or 2, characterized in that: The hard coating layer has a thickness greater than 2.0 μm and less than 6.0 μm.
4. The hard coating film according to claim 1 or 2, characterized in that: The amount of the sesamol-type benzotriazole ultraviolet absorber blended is 20 to 60 parts by mass based on 100 parts by mass of the ultraviolet curable resin of the hard coat layer.
5. The hard coating film according to claim 1 or 2, characterized in that: The transparent substrate is a triacetyl cellulose film, a polyethylene terephthalate film or a cycloolefin polymer film.
6. The hard coating film according to claim 1 or 2, characterized in that: An easy-adhesion layer is provided between the transparent substrate and the hard coating layer.
Citation Information
Patent Citations
Triazine ring-containing polymer and composition for film formation comprising same
WO2013094664A1
Triazine ring-containing polymer and composition for film formation containing same
WO2017110810A1